Sistem Informasi Pengolahan Data Pemagang Berbasis Web - Mela Oktovia; Fauzi Amri; Paula Mia Krisjayanti (LPPM Universitas Bina Sarana Informatika, 2020)
To facilitate the processing of apprentice data, and to provide employee information, software that can process apprentice and employee data is required. Therefore it is necessary to analyze so that it can obtain data for the software being built. It is necessary to analyze user needs and the facilities needed by the software to be built so that it can be useful for users. It is necessary to design software to design a data processing system. This design uses Adobe Dreamweaver CS8 and PHP MyAdmin software to design website-based applications and perform tests using XAMPP. With the existence of a web-based application that can assist in processing apprentice data and provide the information needed by users.